To prepare Learning Experiences to develop Rubber Tapping Competency - Suksom, Khwankamol; Rakthai, Saksri (Journal of Vocational Education in Agriculture, 2024)
The research’s purpose is to design and evaluate the efficiency of a Learning Experience (L.E.) to develop rubber tapping performance regarding rubber tapping methods. The research was provided into 3 steps: 1) to design a L.E. to develop rubber tapping competency with 6 components, 2) to do a trial of L.E. to develop rubber tapping competency, and 3) to improve the L.E. to develop Rubber tapping on inefficient topics. The results was shown that the L.E. for develop rubber tapping competencies was consisted of 3 competencies and 5 learning contents; cognitive competencies at the knowledge content analysis, affective domain aspect of appreciating value in knowledge and psychomotor domain at the practical level until fluent in practical. The experiment’s results of the using L.E. shown that all participants in competency development were able to perform correctly within the specified time. The evaluate’s results of the differences in performance rankings of natural rubber tapping revealed that in the cognitive analysis stage, all competency development participants had high performance rankings that were significantly different (Dmax.cal 0.80 > Dmax.table 0.708), the affective domain of appreciating the importance of holding a rubber tap knife correctly, the participants in competency development ranked their competency at a medium and high level, with no statistical significant difference (Dmax.cal 0.60 < Dmax.table 0.708), the affective domain of appreciating the benefits of tapping rubber correctly and the matter of maintaining rubber tapping knives, all competency development participants had the highest level of competency rankings, with a statistically significant difference (Dmax.cal 0.80 > Dmax.table 0.708) and psychomotor domain until being fluent in how to tap rubber, the competency development participants had high and highest competency rankings. There was no significant difference between them. (Dmax.cal 0.60 < Dmax.table 0.708). The improving’s results of the L.E. to develop rubber tapping competency was found that there was an improvement in the learning situation in the range of skills regarding the rubber tapping method by increasing the rubber tapping practice from 10 taps to 15 taps in order for the participants to develop their competency and have a better performance ranking.